Analisis Kesadaran Dan Literasi Lingkungan Pada Mahasiswa Pendidikan Biologi - Dewi Amelia Widiyastuti; Luthfiana Nurtamara; Almira Ulimaz (Departement of Mathematics Education, 2024)
Environment is one of the materials and topics that are always interesting to discuss in learning. Environmental problems that occur today are increasingly diverse. This is because there is a lot of natural damage due to weather and climate change. Environmental problems are often found in everyday life and can be discussed together in learning by taking real examples that can be found directly in the surrounding nature. The current 21st century learning model emphasizes problem-based learning (PBL) and case-based study as well as project-based learning (PjBL). This research was conducted to analyze how environmental literacy in Biology Education students of FKIP ULM. The research method used is qualitative research by providing instruments in the form of questionnaires related to environmental problems, especially those encountered around which then measured students' understanding of this. The environmental literacy variable is adapted from the NELA environmental literacy variable with the environmental aspects observed, namely verbal commitment, environmental sensitivity, feelings for the environment, issue analysis, issue identification, action plans, and real commitment. The analysis was conducted by looking at the scores obtained by students and seeing the changes that occurred during the pretest and posttest. The results showed an increase in students' environmental literacy, with the highest increase in verbal commitment of 18%. The results of this research provide an overview of how to understand environmental literacy and awareness in students and analyze things that are still lacking and can be improved through other learning models.